A quantitative and qualitative approach on the evaluation of technological pathways: A comparative national-scale Delphi study. (June 2022) - Suominen, Arho; Hajikhani, Arash; Ahola, Antti; Kurogi, Yutato; Urashima, Kuniko
Abstract: The Delphi approach is a central method in technological forecasting. It has been used in thousands of scholarly works and extensively outside academia, often in relatively narrowly scoped case studies. With the notable exception of Japan and a few other countries, broad Delphi studies run in the context of national-level policy planning are seldom seen. This study presents results on implementing the long-running Japanese Science and Technology Prediction Delphi survey developed by the National Institute of Science and Technology Policy (NISTEP) in Finland. This study reports the implementation of the 702 statement Delphi and on the reflections of the expert opinion study against quantitative data on Finnish research capabilities. The differences in expert opinion are discussed between Japanese and Finnish experts and the importance is highlighted that contextual factors play in responses received from the experts even on extremely global issues, such as the development of science and technology. It is proposed that quantitative data can serve as an important contextualization tool for the expert opinion results. Highlights: The research applied NISTEP's Science and Technology Prediction Delphi in Finland. Delphi expert opinions are reflected against quantitative data on Finnish science. Results highlight the need to understand contextual factors when adopting a Delphi study for a different country. The results from Finland show that quantitative data serves as a valuable tool to contextualize results. The results show that a large national-level Delphi is challenging because of the access to experts at scale.